Understanding fuel cell plug-in hybrid electric vehicle use, design, and functionality - Salisbury, Shawn, author; Bradley, Thomas, advisor; Sega, Ronald, committee member; Kirkpatrcik, Allan, committee member (Colorado State University. Libraries, 2014)
The fuel cell plug-in hybrid electric vehicle (FCPHEV) has been shown to be a promising vehicle architecture in terms of cost, emissions reduction, and reducing petroleum use. It combines a high power battery pack and a small fuel cell to make a zero emissions vehicle with all of the capabilities of current consumer vehicles. Previous FCPHEV studies have projected vehicle cost, emissions, and efficiency, but little work has been performed towards understanding the use, design, and functionality of the architecture. This study presents several topics which will help to advance the state of the FCPHEV. Plug-in hybrid vehicles, including FCPHEVs, can use two different sources of fuel depending upon how the vehicle is driven and charged. To quantify this fuel use, SAE J2841 establishes a utility factor method based upon transportation survey data that includes assumptions about vehicle use and battery charging habits. The utility factor model is an important tool for automakers, consumers, and researchers, and it is used by the EPA to determine the fuel economy of plug-in hybrid vehicles. In the Section A of this study, the utility factor model is examined and compared to data collected from over 1,400 Chevrolet Volts in order to assess its accuracy. Until now, there has been no large-scale set of vehicle data to which the model could be compared. Results show that the assumptions of the J2841 utility factor model are not representative of the driving behavior of this set of plug-in vehicles. A hydrogen fueled vehicle requires a high pressure gaseous fuel storage and delivery system that is very different than the fueling systems of current conventional vehicles. The design and execution of the system is critical to the safety and functionality of an FCPHEV, but previous literature on hydrogen fueled vehicles covers fuel systems in little detail. Section B of this study details the considerations that one must make when designing a high pressure hydrogen fuel system and provides an example of how those considerations were met for the FCPHEV built by Colorado State University in the EcoCAR 2 competition. The FCPHEV built for the EcoCAR 2 competition is the first of its kind to publish real-world driving data. Data taken from the vehicle during on-road testing is analyzed in Section C of this study to prove the FCPHEV concept and increase the understanding of overall system operation. The results of the driving tests demonstrate the viability of the FCPHEV and highlight its advantages over current zero emissions vehicle architectures.
Keywords: fuel cell; plug-in hybrid vehicle